Influence of nitrogen and magnesium doping on the properties of ZnO films - 李东华 王惠琼 周华 李亚平 黄政 郑金成 王嘉鸥 钱海杰 奎热西 陈晓航 詹华瀚 周颖慧 康俊勇 (Chinese physics B, 2016)
Undoped ZnO and doped ZnO films were deposited on the MgO（111） substrates using oxygen plasma-assisted molecular beam expitaxy. The orientations of the grown ZnO thin film were investigated by in situ reflection high-energy electron diffraction and ex situ x-ray diffraction（XRD）. The film roughness was measured by atomic force microscopy, which was correlated with the grain sizes determined by XRD. Synchrotron-based x-ray absorption spectroscopy was performed to study the doping effect on the electronic properties of the ZnO films, compared with density functional theory calculations.It is found that, nitrogen doping would hinder the growth of thin film, and generate the NOdefect, while magnesium doping promotes the quality of nitrogen-doped ZnO films, inhibiting（N_2）Oproduction and increasing nitrogen content.